1996
DOI: 10.1111/j.1365-3040.1996.tb00223.x
|View full text |Cite
|
Sign up to set email alerts
|

High salinity tolerance in the stl2 mutation of Ceratopteris richardii is associated with enhanced K+ influx and loss

Abstract: The roles of K+ uptake and loss in the salinity response of the wild type and the salt‐tolerant mutant stl2 of Ceratopteris richardii were studied by measuring Rb+ influx and loss and the effects of Na+, Mg2+, Ca2+ and K+‐transport inhibitors. In addition, electrophysiological responses were measured for both K+ and Rb+ and for the effects of Na+ and NH4+ on subsequent K+‐induced depolarizations. stl2 had a 26–40% higher uptake rate for Rb+ than the wild type at 0.5–10 mol m−3 RbCl. Similarly, membrane depolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Much of this salinization is attributable to the infiltration and accumulation of NaCl (Zhu, 2001; Munns, 2005), often resulting in soil Na + concentrations above 40 mM, and growth suppression in most crops (Munns, 2005). One of the key physiological processes disrupted by Na + supply in this toxic range is the maintenance of cellular and whole-plant potassium homeostasis (Rains and Epstein, 1967; Flowers and Läuchli, 1983; Watad et al , 1991; Gaxiola et al , 1992; Warne et al , 1996; Zhu et al , 1998; Santa-María and Epstein, 2001; Peng et al , 2004; Cakmak, 2005; Kader and Lindberg, 2005; Kronzucker et al , 2006; Takahashi et al , 2007). At the tissue level, the ratio of K + to Na + is considered an excellent indicator of plant tolerance to salinity; the higher the ratio, the higher the plant's tolerance (Flowers and Hajibagheri, 2001; Cakmak, 2005; Chen et al , 2007 b ; cf.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this salinization is attributable to the infiltration and accumulation of NaCl (Zhu, 2001; Munns, 2005), often resulting in soil Na + concentrations above 40 mM, and growth suppression in most crops (Munns, 2005). One of the key physiological processes disrupted by Na + supply in this toxic range is the maintenance of cellular and whole-plant potassium homeostasis (Rains and Epstein, 1967; Flowers and Läuchli, 1983; Watad et al , 1991; Gaxiola et al , 1992; Warne et al , 1996; Zhu et al , 1998; Santa-María and Epstein, 2001; Peng et al , 2004; Cakmak, 2005; Kader and Lindberg, 2005; Kronzucker et al , 2006; Takahashi et al , 2007). At the tissue level, the ratio of K + to Na + is considered an excellent indicator of plant tolerance to salinity; the higher the ratio, the higher the plant's tolerance (Flowers and Hajibagheri, 2001; Cakmak, 2005; Chen et al , 2007 b ; cf.…”
Section: Introductionmentioning
confidence: 99%
“…The potassium target A large number of studies has shown the disruption of both cellular and whole-plant potassium homeostasis under sodium stress (Rains and Epstein 1967a, b, c;Flowers and Läuchli 1983;Watad et al 1991;Gaxiola et al 1992;Warne et al 1996;Zhu et al 1998 Takahashi et al 2007;Kronzucker et al 2008;Britto et al 2010;Coskun et al 2013, cf. Seemann andCritchley 1985).…”
Section: Sodium Toxicitymentioning
confidence: 99%
“…In such soils, NaCl concentrations typically exceed 40 mM, and much higher values are frequently found (Munns 2005), creating toxic growth conditions for most plants, including all major crop species. It has long been known that NaCl toxicity is largely attributable to the effects of Na + , and only rarely those of Cl − , and that Na + toxicity is linked strongly to the plant's ability to sustain the acquisition and in planta distribution of K + (Rains & Epstein 1967;Warne et al . 1996;Zhu, Liu & Xiong 1998;Tyerman & Skerrett 1999;Kader & Lindberg 2005).…”
Section: Introductionmentioning
confidence: 99%